Perancangan Sistem Informasi Penjualan Tabung Oksigen Pada Toko Pan Gas Gombong Berbasis Website - Wijaya, Yosep Fajar; Suparno, Agus; Wibowo, Adhi (INCODING: Journal of Informatics and Computer Science Engineering, 2022)
Pan Gas Gombong Store is a distributor of industrial gas and medical gas that sells gas cylinders. Pan Gas Gombong does not yet have a system to process computerized data, therefore sales data recording is still manual so a lot of sales data is lost, which causes a long time for making sales transaction reports. With the existing problems, an oxygen cylinder sales information system was built at Pan Gas Gombong. System development is carried out using the prototype method, PHP programming language, Codeigniter framework, and MySQL database. This study uses the Wilcoxon Signed Ranks Test, white box testing, and black box testing. Testing the benefits in the aspect of efficiency using the ISO 9126 standard, it was found that 60% of respondents answered agree and strongly agree. Based on this, it can be concluded that the oxygen cylinder sales information system at Pan Gas Gombong can speed up the process of making sales reports.